2022
DOI: 10.1097/aog.0000000000004675
|View full text |Cite
|
Sign up to set email alerts
|

Racism and the Reproductive Health Experiences of U.S.-Born Black Women

Abstract: For some participants, these racialized experiences affected their sexuality throughout their lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Our findings about the challenges involved in obtaining reproductive health care, particularly the need for self‐advocacy and being highly involved in directing their own care, aligned with a study by Treder et al who identified medical racism and “self‐protective actions when interacting with the reproductive health care system.” 51 The authors concluded that “self‐protective actions” such as seeking out providers of color, overpreparing for appointments, and finding advocates were triggered by experiences with racism and “promot[ed] safety, autonomy and rehumanization within a system that has historically and contemporarily devalued Black reproductive health.” 51 Future researchers in this area will need to acknowledge and work with the strength of these self‐protective actions while at the same time working with communities to develop innovative strategies that improve quality of care and promote trust. Based on our findings, coordinated care models with peer navigators is one such innovation 52 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings about the challenges involved in obtaining reproductive health care, particularly the need for self‐advocacy and being highly involved in directing their own care, aligned with a study by Treder et al who identified medical racism and “self‐protective actions when interacting with the reproductive health care system.” 51 The authors concluded that “self‐protective actions” such as seeking out providers of color, overpreparing for appointments, and finding advocates were triggered by experiences with racism and “promot[ed] safety, autonomy and rehumanization within a system that has historically and contemporarily devalued Black reproductive health.” 51 Future researchers in this area will need to acknowledge and work with the strength of these self‐protective actions while at the same time working with communities to develop innovative strategies that improve quality of care and promote trust. Based on our findings, coordinated care models with peer navigators is one such innovation 52 …”
Section: Discussionmentioning
confidence: 99%
“…22 In a qualitative study, Treder and colleagues explored the reproductive health experiences of US-born Black women. 23 One participant said, "If I felt like someone's already prejudiced before they even see me, before they even look at my chart, I'm not going to show up." For too many birthing people, healthcare is a place of last resort rather than a source of ongoing support.…”
Section: Critically Assess Policies and Practices To Replace Embedded...mentioning
confidence: 99%
“…As Laurie Zephryin writes, disparities in maternal morbidity and mortality are the legacy of systemic racism and the “hierarchy of human value entrenched in policies and practices affecting health and health care” 22. In a qualitative study, Treder and colleagues explored the reproductive health experiences of US-born Black women 23. One participant said, “If I felt like someone’s already prejudiced before they even see me, before they even look at my chart, I’m not going to show up.” For too many birthing people, healthcare is a place of last resort rather than a source of ongoing support.…”
Section: Critically Assess Policies and Practices To Replace Embedded...mentioning
confidence: 99%
“…Operationalizing diverse forms of racism is essential to dismantling inequities in maternal and perinatal health and is a necessary step toward reproductive health justice for Black women in the United States (U.S.). Despite the well-known negative association between racism and health outcomes among U.S. minority racial groups [1,2], scant research exists examining the associations between internalized racism and stress and their impact on maternal mental health and birth outcomes [3]. This limitation is problematic.…”
Section: Short Commentarymentioning
confidence: 99%
“…Internalized racism is the unconscious appropriation of the dominant White culture's actions, beliefs, and stereotypes about racialized peoples [3]. Not to be mistaken for individual pathology, it takes shape through frequent and enduring exposure to multiple…”
Section: Short Commentarymentioning
confidence: 99%